2021
DOI: 10.33137/ijidi.v5i3.36159
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Linguistic Diversity and Inclusion

Abstract: Using a lingua franca for scholarly communication offers some advantages, but it also limits research diversity, and there is a growing movement to encourage publication in other languages. Both approaches require scholars to access material through other languages, and more people are turning to machine translation to help with this task. Machine translation has improved considerably in recent years with the introduction of artificial intelligence techniques such as machine learning; however, it is far from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Strategies for creating inclusive communication channels include Providing a variety of communication channels such as email, instant messaging, video conferencing, and in-person meetings, accommodating different communication preferences, and ensuring accessibility for all employees (Baym et al, 2021). Ensuring that communication materials, including documents, presentations, and training materials, are available in multiple languages or easily translatable promotes inclusivity and facilitates understanding among employees with diverse linguistic backgrounds (Bowker, 2021). Establishing feedback mechanisms encouraging employees to share their perspectives, concerns, and suggestions fosters a culture of openness and inclusivity, allowing diverse voices to be heard and valued.…”
Section: Effective Communication Strategies By Facilitating Cross-cul...mentioning
confidence: 99%
“…Strategies for creating inclusive communication channels include Providing a variety of communication channels such as email, instant messaging, video conferencing, and in-person meetings, accommodating different communication preferences, and ensuring accessibility for all employees (Baym et al, 2021). Ensuring that communication materials, including documents, presentations, and training materials, are available in multiple languages or easily translatable promotes inclusivity and facilitates understanding among employees with diverse linguistic backgrounds (Bowker, 2021). Establishing feedback mechanisms encouraging employees to share their perspectives, concerns, and suggestions fosters a culture of openness and inclusivity, allowing diverse voices to be heard and valued.…”
Section: Effective Communication Strategies By Facilitating Cross-cul...mentioning
confidence: 99%
“…However, using such tools in an informed and critical way is less simple. Therefore, students in general (Bowker, 2021a) and language learners (Carré et al, 2022) should acquire literacy related to MT, not least because research has shown that students who are trained in how MT works perform significantly better when using MT for writing tasks (O'Neill, 2019). The fact that training matters is also emphasized by Vold who concludes that "training, scaffolding techniques and guidance from the teacher are of paramount importance" (Vold, 2018, p. 89) when integrating MT into foreign language teaching.…”
Section: Digital Literacies and Learningmentioning
confidence: 99%
“…For instance, it can have negative implications for the student-teacher relationship, and students might be using MT tools in non-optimal and inappropriate ways which might hinder learning. Therefore, several scholars have argued that students should be trained in how MT works (e.g., O'Neill, 2019;Vold, 2018) equipping them with so-called machine translation literacy (Bowker, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Az utóbbi években egyre szélesebb körben hivatkoznak (Bowker & Buitrago Ciro, 2019;O'Brien & Ehrensberger-Dow, 2020;Bowker, 2021;Liu et al, 2022;EMT, 2022) az MT literacy fogalmára, amely a tudatos MT-használathoz szükséges ismereteket, készségeket és attitűdöket foglalja magában. Bowker & Buitrago Ciro (2019, p. 88) definíciója szerint az MT literacy elemei a következő három kérdés körül artikulálódnak:…”
Section: Módszertani Javaslatok a Tudatos Mt-használathozunclassified